PENERAPAN PERATURAN KEJAKSAAN NO 15 TAHUN 2020 TENTANG PENGHENTIAN PENUNTUTAN BERDASARKAN PENDEKATAN RESTORATIVE JUSTICE PERKARA TINDAK PIDANA PENGGELAPAN DI KEJAKSAAN NEGERI BULELENG - Maharta, Komang Urip Sidi; Landrawan, I Wayan; Hartono, Made Sugi (Judge : Jurnal Hukum, 2026)
This study aims to investigate and improve the implementation of Law No. 15 of 2020. Using qualitative legal research methodology, this study applies data collection techniques such as document review and analysis, field observation, and in-depth interviews. This study has a qualitative case study design and uses document review and analysis, observation, and in-depth interviews as data collection methods. Targeted sampling was used to identify sources of information and key informants. The findings show that the implementation of the Attorney General's Circular Regulation No. 15 of 2020 (regarding Article 5 in the Buleleng District Attorney's Office) has yielded positive results. However, to further develop this procedure, public awareness and legal aid functions must be strengthened. A number of challenges arose during implementation, including the defensive attitude of defendants and compensation claims from prosecutors that often exceeded actual losses, which hindered the effective implementation of restorative justice.